Coronary artery bypass grafting in patients with concomitant solid tumours: early and long-term results. (31st May 2020) - Garatti, Andrea; D'Ovidio, Mariangela; Saitto, Guglielmo; Daprati, Andrea; Canziani, Alberto; Mossuto, Eugenio; D'Oria, Veronica; Scarpanti, Matteo; De Vincentiis, Carlo; Parolari, Alessandro; Menicanti, Lorenzo
Abstract: OBJECTIVES: Our goal was to analyse a consecutive series of patients with solid organ tumours undergoing coronary artery bypass grafting (CABG) by defining the risk factors for early and long-term outcomes. METHODS: Between 2005 and 2016, a consecutive series of 4079 patients underwent isolated CABG at our institution. Of 103 patients (2.5%) with active malignancy, we enrolled 82 patients (mean age 71 ± 7 years) with solid organ tumours, divided into 4 subgroups: lung (9 patients—11%), gastroenteric (16 patients—20%), urinary (48 patients—58%) and other solid tumours (9 patients—11%). A deterministic record linkage between the clinical database and the National Hospital Information System allowed identification of long-term survival rates and freedom from major adverse cardiovascular events (acute myocardial infarction, repeated admissions for percutaneous coronary intervention and heart failure). RESULTS: The most common forms of cancer were prostate, colon and carcinoma of the lung. Compared to patients without cancer, patients with neoplasms were significantly older and had a higher rate of comorbidities, without significant differences among the cancer subgroups. The 30-day mortality rate was significantly higher in patients with cancer compared to those without cancer (4.9% vs 1.8%). However, on logistic regression analysis, cancer was an independent risk factor for postoperative pulmonary dysfunction but not for in-hospital death. The median follow-up time was 58 ± 12 months. The overall 5-year survival rate was 60% [95% confidence interval (CI) 47–71%], with a dismal 32% (95% CI 5–65%) survival rate among patients who had lung tumours only. The 5-year freedom from major adverse cardiovascular events was 64% (95% CI 52–74%), without significant differences among subgroups, and was comparable to that of the non-cancer population. Resolution of coronary heart disease allowed safe cancer surgical resection in 80% of the population. CONCLUSIONS: Based on the results from the present study, CABG should not be denied to patients with solid organ tumours by claiming a worse prognosis or less graft durability. Further studies with larger numbers are warranted.